Pengembangan Aplikasi Android Guizzer sebagai Media Pembelajaran Matematika untuk Siswa Kelas V Sekolah Dasar - Ningkrum, Indriyani; Riswari, Lovika Ardana; Najikhah, Fatikhatun (Nusantara: Jurnal Pendidikan Indonesia, 2024)
Purpose – This research aims to determine the feasibility of the Android-based "guizzer" application in mathematics learning for fifth grade elementary school. The lack of teacher innovation in the use of learning media, especially mathematics, makes students less enthusiastic. Therefore, researchers developed an Android-based Guizzer application to improve the quality of fifth grade elementary school mathematics learning.Method – This research uses Research and Development (R&D) research with the ADDIE development model including the Analyze, Design, Development, Implement and Evaluate stages. This research was carried out at Waturoyo State Elementary School with the research subject being class V. Data collection techniques used included observation, interviews and questionnaires. The data analysis used is in the form of validity.Findings – The research results show that the results of media validation by validator 1 were 78.3% and validator 2 were 85%, resulting in an average of 81.65% (very feasible). The results of material validation by validator 1 obtained a percentage of 83.3% and validator 2 of 81.7%, so an average of 82.5% was obtained (very feasible). The results of the trial, namely student responses, obtained a percentage of 97.1% (very feasible). It can be concluded that the "guizzer" application is very suitable for use in the learning process. Research Implications – Based on the research results, the Android application "Guizzer" is suitable for use in the fifth grade elementary school mathematics learning process. The implication is that students are interested and enthusiastic in the learning process, thereby making a positive contribution to achieving learning goals.